Do Younger Researchers Assess Trustworthiness Differently when Deciding what to Read and Cite and where to Publish? - Nicholas, David; Jamali, Hamid R.; Watkinson, Anthony; Herman, Eti; Tenopir, Carol; Volentine, Rachel; Allard, Suzie; Levine, Kenneth (International Journal of Knowledge Content Development & Technology, 2015)
An international survey of over 3600 academic researchers examined how trustworthiness is determined when making decisions on scholarly reading, citing, and publishing in the digital age and whether social media and open access publications are having an impact on judgements. In general, the study found that traditional scholarly methods and criteria remain important across the board. However, there are significant differences between younger (age 30 & under) and older researchers (over 30). Thus younger researchers: a) expend less effort to obtain information and more likely to compromise on quality in their selections; b) view open access publishing much more positively as it offers them more choices and helps to establish their reputation more quickly; c) compensate for their lack of experience by relying more heavily on trust markers and proxies, such as impact factors; d) use all the outlets available in order to improve the chances of getting their work published and, in this respect, make the most use of the social media with which they are more familiar. URL: http://ijkcdt.net/xml/05533/05533.pdf